Drone Emprit Academic on Religious Studies: Uncovering Netizen's Appraisal - Ai Yeni Yuliyanti; Retno Yuliati (CONTEMPLATE: Jurnal Ilmiah Studi Keislaman, 2025)
The emergence of social media causes religious authorities to shift the possibility for everyone to talk about religion. On August 21, 2021, a YouTuber named Muhammad Kece was reported for blasphemy related to content he made on his Youtube channel. This study aims to determine netizens' behavior on social media, precisely the public response to the alleged Islamic blasphemy by a YouTuber named M. Kece. This research uses quantitative content analysis by the proposed project to the Drone Emprit Academic (DEA) to capture all mentions maps from Twitter conversations from September 26, 2021, until October 2, 2021. The results show that the public response toward the alleged Islamic blasphemy of Youtuber M. Kece is mostly negative rather than positive. Based on most retweet data, people are more interested in the accompaniment of M. Kece by Irjen Napoleon Bonaparte than in his blasphemy case. On the other hand, the tweet is about the person who tries to drag Ust. Abdul Somad, in that case, is the most favorite tweet. Then, followed by the case of blasphemy committed by M. Kece precisely about who M. Kece is. It shows that the case of the alleged Islamic blasphemy of Youtuber M. Kece is complicated and complex because it was religion followed by another case. Irjen Napoleon's accompaniment to him. Thus, be wise in social media as a consumer or a content creator, especially about religion.